Conception and early pregnancy in the mare: lipidomics the unexplored frontier - Edwina F Lawson; Christopher G Grupen; Mark A Baker; R John Aitken; Aleona Swegen; Charley-Lea Pollard; Zamira Gibb (Bioscientifica, 2022)
Lipids are dynamic biological molecules that play key roles in metabolism, inflammation, cell signalling and structure. They are biologically significant in the physiology of conception and reproduction. Many of the mechanisms surrounding equine conception and the early feto-maternal dialogue are yet to be understood at a biochemical level. Recently, lipidomic technologies have advanced considerably and analytical strategies have been enhanced and diversified. Consequently, in-depth lipidomic exploration now has the potential to reveal new lipid biomarkers and biochemical relationships that improve our understanding of the processes leading to efficient and successful reproduction. This review considers the role of lipids in conception and establishment of pregnancy, providing new insights into the enigmatic pathways governing early reproductive physiology of the mare.